1997
DOI: 10.1093/humrep/12.12.2654
|View full text |Cite
|
Sign up to set email alerts
|

The effect of training and duration of surgery on adhesion formation in the rabbit model

Abstract: In order to evaluate the effect of training upon postoperative adhesions, standard bipolar and mechanical, nonopposing injuries were performed in the uterine horns and side walls of 52 mature female rabbits using a conventional three-puncture laparoscopy, by an endoscopic surgeon with limited experience. An additional injury, either bipolar or mechanical or both, was performed in the retro-uterine space. With experience, the duration of surgery decreased progressively from 12 +/- 2 to 8 +/- 1 min in the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
18

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 19 publications
3
24
0
18
Order By: Relevance
“…Carbon dioxide pneumoperitoneum affects the intraperitoneal environment and was described as a factor, which in standard conditions during short time laparoscopy, influences the peritoneum and promotes the formation of adhesions. However, heating the gas may limit this process [31][32][33][34]. Molinas et al [35] studied mice peritoneum and observed that an increased formation of adhesions correlates with the duration and pressure of pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon dioxide pneumoperitoneum affects the intraperitoneal environment and was described as a factor, which in standard conditions during short time laparoscopy, influences the peritoneum and promotes the formation of adhesions. However, heating the gas may limit this process [31][32][33][34]. Molinas et al [35] studied mice peritoneum and observed that an increased formation of adhesions correlates with the duration and pressure of pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…These species are excellent to quantify adhesion formation at a minimum interval of 7 days. Rabbits are an animal model that is favorable for adhesion formation, mainly because they are easily adaptable to videolaparoscopic procedures with conventional equipment, such as nephrectomies and Nissen's operation 12,13 . The fibrinolitic potential of the peritoneum is variable among animal species, and there is more plasminogen activation in the rabbit than in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…After abdominal surgery, adhesion formation seems to be one of the major pathologic changes in almost all cases [12]. In comparison with open surgery, laparoscopic surgery, as a minimally invasive technique, seems to have a marked effect in the reduction of adhesion formation.…”
Section: Discussionmentioning
confidence: 99%